Hambatan Ontogenik dalam Kurikulum Akidah: Konstruksi Model Tadarruj Kognitif Berbasis Jean Piaget dan Ibn Khaldun - Faqih Abdul Aziz; Rohmat Robi’ Rozaqiy; Irfan Tamwifi; Akhtim Wahyuni (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2026)
The Akidah (Islamic theology) curriculum at the Madrasah Ibtidaiyah level frequently demands a high degree of deductive abstraction that directly conflicts with the concrete operational stage of primary school-aged children. This study aims to respond to the latest regulatory framework, the Decree of the Minister of Religious Affairs (KMA) Number 1503 of 2025, which demonstrably overlooks cognitive readiness parameters. The absence of such cognitive calibration instruments generates a structural mismatch that triggers ontogenic obstacles, particularly the manifestation of tajsim (anthropomorphic) misconceptions in the classroom. Utilizing a library research design with qualitative content analysis and policy document analysis approaches, this study synthesizes Brousseau’s theory of didactical situations, Piaget’s stages of cognitive development, and Ibn Khaldun’s epistemology of tadarruj (gradualism). The findings demonstrate that the centralized curriculum documents prematurely impose eschatological-metaphysical reasoning upon students. As an alternative resolution, this study constructs the